Development of vocal communication in children with autism spectrum disorder during improvisational music therapy. Issue 3 (27th May 2019) - Salomon-Gimmon, Maayan; Elefant, Cochavit
ABSTRACT: This preliminary study examined vocal communication in children with autism spectrum disorder during improvisational music therapy. It investigated trends and patterns of vocal development, and identified and categorized vocal interventions during music therapy sessions. The research is based on rigorous‎ video microanalysis of 4 cases of children who received music therapy over the course of 5 months. One session per month was analyzed for each case, yielding data from a total of 20 sessions. The cases and sessions were selected based on a purposeful sample strategy, so as to choose materials with apparent vocal expressions that are likely to illuminate the focus of the investigation. ‎The findings revealed that, in most cases, vocal communication developed over the course of the music therapy sessions and that this development is not linear, but rather is characterized by complex development patterns. In addition, 16 key vocal interventions used by the music therapists throughout the treatments were categorized.